2019
DOI: 10.1007/s10924-019-01392-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biorenewable Composites Based on Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) with Natural Fillers

Abstract: Due to the ubiquity and single-use character of plastic products, their production represents a burden to the environment. Therefore, an increasing interest in biodegradable and bio-compostable materials has been observed in the recent years. Bio-based materials are becoming more and more popular, especially in applications where biodegradability provides an advantage for customers and environment. However, biodegradable materials are more expensive compared with durable plastic materials, so to reduce costs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 45 publications
6
19
0
1
Order By: Relevance
“…Up to 1000 h of exposure, an increase in the crystallinity of PHBV was observed, but a decrease was observed after 2000 h, while PHBV/TiO 2 just showed a slight increase after 500 h of weathering exposure. This behavior in the crystallinity index of the samples suggests that the degradation of neat PHBV occurred preferentially in the amorphous phase, leading to chain rearrangement and re-crystallization [ 25 , 26 , 94 ], as was already suggested by the other results. A decrease in the crystallinity index after a long time of degradation exposure was observed, because the non-amorphous phase was also attacked and destroyed.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Up to 1000 h of exposure, an increase in the crystallinity of PHBV was observed, but a decrease was observed after 2000 h, while PHBV/TiO 2 just showed a slight increase after 500 h of weathering exposure. This behavior in the crystallinity index of the samples suggests that the degradation of neat PHBV occurred preferentially in the amorphous phase, leading to chain rearrangement and re-crystallization [ 25 , 26 , 94 ], as was already suggested by the other results. A decrease in the crystallinity index after a long time of degradation exposure was observed, because the non-amorphous phase was also attacked and destroyed.…”
Section: Resultsmentioning
confidence: 54%
“…It is shown that the intensity of the amorphous bands for the neat PHBV decreased over the exposure time. In studies on PHBV exposed to moisture, thermal, and UV conditions, degradation was reported to start in the amorphous phase and then to proceed into the crystalline phase [ 25 , 26 , 94 ]. The results shown in Table 1 reveal that the degradation of neat PHBV under moisture and UV exposure occurs preferentially in the amorphous phase, as evidenced by the decrease in the corresponding carbonyl index.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, PHBV with very low mol% of 3-HV was reported to be with tensile strength 36.2 MPa and elongation at break 1% (Jost and Miesbauer 2018). The PHBV obtained from the PHB10 was having better mechanical properties than PHBV reported by Kuciel et al (2019). The values are in a range suitable for tissue engineering applications (Little et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Similar relations were observed in our previous work on PHBV-based composites with natural fillers. [27] Generally, no major differences were found in the mechanical properties between the neat polymers and their composites with added antibacterial particles. As also shown in other studies, Ag particles incorporated in a polymer matrix did not make important contributions to mechanical properties.…”
Section: Tensile and Bending Propertiesmentioning
confidence: 96%